PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN RESILIENSI SISWA KELAS X IPA SMA NEGERI 5 PEKANBARU - Uli bashirah Uli bashirah; Elni Yakub Elni Yakub; Raja Arlizon Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) to assess the resilience of students before being given guidance services group, 2) to assess the process of implementation guidance services group to increase the resilience of the students, 3) to determine the increase resilience students after being given guidance services group, 4) to determine differences in resilience students before and after the given group counseling services, 5) to determine how much influence the group counseling services to increase the resilience of the student. The method used is an experimental method to design one group pretest-posttest design. The subjects were students of class X IPA SMAN 5 Pekanbaru totaling 30 students. To collect the data used purposive sampling technique. To distinguish the resilience of students before and after the group guidance services using the test "t" is obtained thitung price greater than ttable with significance level of 5% (2.48> 2.000). Thus Ho was rejected and Ha was accepted, which means there are significant differences to the increased resilience of the students before the post given group counseling services. Then the results of the test product moment r = 0.60 and coefficient of determination r2 = 0.36. Based on the results of research conducted it can be concluded that once implemented and group counseling services to students of class X resilience IPA SMAN 5 Pekanbaru increased by 36%.Key Words: Guidance Services Groupe, Resilience